(untitled) (Medical Forum Monthly, 2024)
Objective: The main objective of the present study is to determine the histopathological patterns and diagnostic value of endometrial curettings in patients presenting with abnormal uterine bleeding. Study Design: A prospective study Place and Duration of Study: This study was conducted at Department of Pathology Liaquat University of Medical and Health Sciences Jamshoro during March 2010 to February 2011. Materials and Methods: A total of 100 cases of endometrial curettage were processed for routine staining with Haematoxylin and Eosin and slides were evaluated for histopathological diagnosis. Results: The results showed that patient’s age ranged between 40-52 years and most of the patients about 77% presented with menorrahgia. The histological findings showed normal phase (Proliferative and Secretory phase) of menstrual cycle in 52% of cases followed by simple hyperplasia without atypia 23%, chronic endometritis 13%, polyp 2%, tuberculous endometritis 2%, anovulatory cycle 1%, anovulatory cycle with chronic endometrits 1%, atrophic changes 1%, atypical complex hyperplasia 2% and malignancy in 3% of cases. The Simple hyperplasia 23% and chronic endometritis 13% were the commonest pathological alteration. The accidental findings of organic lesions including polyps and malignancy in 5% cases focused the diagnostic importance of curettage in patients presenting with abnormal uterine bleeding. Conclusion: It is concluded that simple hyperplasia without atypia and chronic endometritis are most important causes of abnormal uterine bleeding in the perimenopausal age groups.